Developmental Analysis of Compound Leaf Development in Arachis hypogaea - Sun, Ruiqi; Peng, Zhenying; Li, Shuangshuang; Mei, Hongyao; Xu, Yiteng; Yang, Wenying; Lu, Zhichao; Wang, Hongfeng; Zhang, Jing; Zhou, Chuanen (Frontiers in Plant Science, 2022)
Leaves are the primary photosynthetic structures, while photosynthesis is the direct motivation of crop yield formation. As a legume plant, peanut (Arachis hypogaea) is one of the most economically essential crops as well as an important source of edible oil and protein. However, the molecular mechanism underlying A. hypogaea leaf development remains elusive. The leaves of A. hypogaea are in tetrafoliate form, which is different from the trifoliate leaf pattern of Medicago truncatula, a model legume species. In A. hypogaea, a pair of terminal leaflets were developed, however, only one terminal leaflet was formed in M. truncatula. In this study, the compound leaf development in A. hypogaea was investigated. Transcriptomic profiles revealed that the common and unique different expression genes were identified in lateral leaflets and terminal leaflets, which provide a significant research route to deeply understand the underlying mechanism in A. hypogaea leaf development. Then, a mutant line with leaf developmental defects in A. hypogaea was obtained, which shows pentafoliate form with an extra terminal leaflet. Characterization of the mutant indicates that cytokinin and class I KNOTTED-LIKE HOMEOBOX are involved in control of compound leaf patterns in A. hypogaea. These results expand our knowledge and provide insights into the molecular mechanism underlying the formation of different compound leaf patterns among species.